Improving Land Sector Governance in the Philippines - Eleazar, Floradema C.; Garcia, Brian; Guiang, Ernie; Herrera, Annabelle; Isorena, Lina D.; Ravanera, Roel; Serote, Ernesto (World Bank, Washington, DC, 2017)
Land is a vital resource for any nation. It serves as the platform for carrying out social, cultural, and economic activities. The land governance assessment framework was developed by World Bank and its partners to provide a tool for diagnosis of land governance issues, establish benchmarks, and monitor progress over time. It comprises a set of detailed indicators to be rated on a scale of pre - coded statements. The process helps to establish a consensus and priority actions on: (i) gaps in existing evidence; (ii) areas for regulatory or institutional change; and (iii) criteria to assess the effectiveness of these measures. This document represents the country report for the Philippines. It describes the process for implementation and the country context. The assessment of land governance is also presented, as well as the policy analysis, conclusions, and recommendations. The report is intended to serve as a reference guide for government and other land practitioners in non-government organizations, private sector, academe, and other groups to help shape the direction, focus, and support for the land sector, and how progress in improving governance can be effectively monitored.